Prosodic phrasing and the emergence of phrase structure - Himmelmann Nikolaus P. (Linguistics, 2022)
To clarify the role of prosodic phrasing in the emergence of phrase structure, it is necessary to be clear as to how syntactic phrasing relates to prosodic phrasing. The core proposal here is that a distinction must be made between two basic types of syntactic constructions; namely, syntactic configurations for which prosodic phrasing is part of the definition of the construction, and phrase structure proper, which is independent of prosodic phrasing. This distinction implies a somewhat more complex view of the interface between syntax and prosody than is currently widely assumed. Rather than conceiving of prosodic phrases as derivative of syntactic phrases, prosodic phrasing and syntactic phrase structure are seen here as alternative ways of relating words to each other, forming larger units from smaller ones. Against this background, the emergence of phrase structure is conceived of as the emancipation of syntax from prosodic scaffolding.